Deep learning-based self-interference cancellation for full-duplex network - Tan, Jiayu (Nanyang Technological University, 2023)
Comparing full-duplex systems to time-division duplex and frequency-division duplex systems, the efficiency of spectrum use can be theoretically doubled. It is one of the development directions of next-generation wireless communication technologies. One of the critical issues to be addressed in full-duplex systems is the self-interference generated by their own transmitted signals, which can affect the correct demodulation of useful signals.